# simplify is not realible

12 views (last 30 days)

Show older comments

How to simplify the folowing very simple expression:

syms a b c

e1 = -(b*(b^2 - 4*a*c)^(1/2) - 4*a*c + b^2)/(2*a*(b^2 - 4*a*c)^(1/2))

which is equal to the

e2 = -(b + (b^2 - 4*a*c)^(1/2))/(2*a)

simplify(e1-e2)

ans =

0

>> isAlways(e1 == e2)

ans =

logical

1

but

simplify(e1)

produce only identical expression with "e1", not with "e2" as expected?!

Is there any possibility to use "simplify" command in a different way, to get expected result?

##### 7 Comments

John D'Errico
on 31 Mar 2023

### Answers (0)

### See Also

### Categories

### Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!